Gawan Mewah dalam Perkawinan Masyarakat Jawa di Desa Sidomulyo, Pati: Antara Pranata Budaya, Bahasa Simbolik, dan Negosiasi Adat–Syariah - Umdatun Nikmah (Journal of Nahdlatul Ulama Studies, 2024)
This study examines the wedding gift tradition (gawan), which tends to be luxurious, in Sidomulyo Village, Jakenan Subdistrict, Pati Regency. This tradition is not merely a cultural procession; it also constructs standards of propriety and symbols of honor, and may generate socio-economic pressure through the stigma of “ora elok/walak” when these expectations are not fulfilled. The study addresses two research questions: (1) how the luxurious gawan tradition is practiced and interpreted as a cultural institution and a “symbolic language” in Javanese marriage; and (2) how luxurious gawan practices negotiate the relationship between custom and Islamic law (the distinction between mahar and gawan) and their implications for norms of propriety and socio-economic burdens. Using a qualitative case-study design, data were collected through observation, semi-structured interviews, and documentation, and analyzed through data reduction, presentation, and verification. The findings show that gawan is delivered before/during the marriage contract (akad nikah) in the form of household furniture, bedroom items, kitchenware, cosmetics, and even high-value goods such as vehicles or livestock, which are publicly displayed. Gawan is understood as a form of respect for the bride and a sign of the groom’s readiness; however, its luxurious nature may shift into a status marker that increases financial burdens and narrows the space for negotiation. The distinction between mahar (a mandatory Islamic obligation) and gawan (customary/negotiated practice) often becomes blurred when gawan is treated as a social obligation; in cases of divorce, the return of gawan reveals issues of ownership and power relations over assets. In conclusion, gawan in Sidomulyo strengthens cultural identity and social solidarity, but it may cause harm if imposed as an oppressive social obligation. This study recommends strengthening community literacy regarding the Islamic distinction between mahar and gawan; encouraging family deliberation to set realistic gawan standards based on financial capacity; and establishing written agreements on the ownership status of gawan, including arrangements in the event of divorce, so that the tradition remains meaningful without becoming an instrument of pressure.